New Habits Adaptation Associated with the Mental Health among Tourism Drivers During Covid-19 Pandemic - I Gusti Ayu Putu Satya Laksmi; Desakmadearidwijayanti (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Increased mental health problems during the Covid 19 pandemic. Objective: This research aims to find the relationship between the Adaptation of New Habits and the mental health of tourism drivers during the Covid-19 pandemic. Method: Correlation quantitative descriptive research design with a cross-sectional approach. The population is the tourism driver United Bali Driver a total of 545 people, a total sample of 231 people using the Slovin formula with the purposive sampling method. The measuring instrument used is the  New Habits Adaptation and SRQ questionnaires. Data analysis using rank spearmen test. Result: Mental health showed emotional and mental disorders, psychotic disorders, and Post-traumatic stress disorder. Test results of the New Habit Adaptation variable analysis with cognitive and emotional disorders p value 0.004 (p 0.05). Variable Adaptation to New Habits with psychotic disorders p value 0.700 (p?0.05). Variable Adaptation to New Habits with Post-traumatic stress disorder p value 0.700 (p?0.05). Conclusion: There is a relationship between the Adaptation of New Habits with Mental and Emotional Disorders. This is due to the same perception and feeling about the stressor experienced. There is no relationship between Adaptation to New Habits with Psychotic Disorders and Post Traumatic Stress Disorder. Recommendation: This is due to problems that were felt to have occurred before the Covid-19 pandemic. It is advisable to adopt new habitual adaptations to maintain mental health